PENGARUH KARAKTERISTIK PETANI TERHADAP PENDAPATAN PETANI KELAPA SAWIT (Studi Kasus : Desa Lau Mulgab, Kecamatan Selesai, Kabupaten Langkat ) - Nasution, Myrna Pratiwi (Agriprimatech, 2023)
The aim of this research is to analyze the influence of education, land area, farmer experience, farmer age and number of family on the income of oil palm farmers in Lau Mulgab Village, Selesai District, Langkat Regency. The analytical method used is multiple linear regression analysis with SPSS Version 22 tools. The sampling method uses a simple random sampling technique which means that each element of the population has an equal opportunity to be sampled. The data collection methods used were observation, questionnaires, interviews and documentation. The research results show that the variables education, land area, farmer experience, farmer age, and number of family have a significant effect on the variable income of oil palm farmers (via the F test). And the results of the partial test (t test) show that the variables of education and number of family do not have a significant effect on the income of oil palm farmers in Lau Mulgab Village, Selesai District, Langkat Regency, while land area, farmer experience, farmer age have a significant effect on the income variable of coconut farmers. palm oil in Lau Mulgab Village, Selesai District, Langkat Regency.